Development of magnetic sensor seismic instrumentation - 225328 Rashdi Shah Ahmad; Azlan Adnan; Mohd. Rosaidi Che Abas, 1958-; Asia Pacific Structural Engineering and Construction Conference (5th : 2003 : Johor) (Skudai : Universiti Teknologi Malaysia, 2003)
09